Meanings of community: Educational developers experience care, satisfying contributions, and belonging in a collaboration across institutions - Daniel Mann; Darren S. Hoffmann; Katherine Kearns; Thomas Matthew Colclough; William James Howitz (To Improve the Academy, 2023)
We share insights from a mixed methods study to describe the experience of educational developers participating in a community of practice (CoP). This CoP consisted of 19 leaders at eight institutions, serving collectively as facilitators of a hybrid, across-institutional, seven-week workshop series on course design for graduate students and postdoctoral scholars. From results of a survey examining the functional and sustaining features of the community, we illustrate that members experience the community aspect of our CoP primarily as a sense of satisfaction/personal fulfillment and, to an extent, in the effectiveness/productiveness of collaborations between members. Members of our CoP experience several community-related benefits specific to their across-institution collaborations. We demonstrate the importance of members’ sense of belonging, overall professional development, and well-being for sustaining our CoP.